Presence of Peregrinus maidis in Azuero corn production areas, Panama - Atencio - Valdespino, Randy (2026)
Introduction. The corn delphacid, Peregrinus maidis (Ashmead) (Hemiptera: Delphacidae), is an insect of economic importance for corn production, as it causes direct damage to the plant and acts as a vector of several viruses. Objective. To determine the distribution of corn delphacid in the corn production zones of the Azuero peninsula, Panama. Materials and methods. During November and December 2024, fourteen locations with corn plantations in Los Santos province, located on the Azuero peninsula, Panama, were surveyed. The plantations were in the phenological stage of maturation. At each location, twenty corn plants were randomly inspected. The leaf located at the node where the ear develops was selected as the sampling unit to search for suspected P. maidis specimens, which were captured using a brush, 70 % alcohol, and 11 mL vials with caps. The collected specimens were identified using taxonomic keys, and the number of nymphs and adults (males and females) was quantified. Results. The corn delphacid was detected at all fourteen locations. A total of 473 specimens were captured, of which 441 were adults (235 females and 206 males) and 32 immatures. Conclusions. P. maidis is widely distributed in the corn production area of the Azuero peninsula, so it is important to monitor its population dynamics.